Teoria da potência conservativa aplicada ao compartilhamento de responsabilidades sobre as distorções harmônicas de tensão - Menezes, Luciano Jorge (2022)
In the last decades a continuous increase in harmonic voltage distortions in the electrical system has been verified, whether in the generation, transmission or distribution levels. This fact occurs mainly due to the insertion of non-linear loads in several points of the electrical system. As positive highlights of the application of electrical equipment that generate distorted currents, the technological advance and the increase in productivity can be mentioned. However, these same loads, in most cases, are sensitive to the disturbances they generate. In this context, when the harmonic distortion limits are above the maximum allowed by the normative, there is the concern to hold responsible those who contribute to the deterioration of the power quality, indicating those who should financially pay for possible mitigating actions, which, in general, can be the implementation of tuned passive filters, active filters or hybrid filters. However, such corrections are costly in financial terms. As a consequence of this, the issue of sharing responsibility for harmonic distortions arises, which seeks to determine the origin of the disturbance, since harmonic distortion is the result of the interaction between several sources of disturbance. For the determination of the responsibility percentages, several methodologies have been developed, however, procedures capable of combining mathematical precision and practical application are still lacking. Some methods have strong mathematical consistency, but are difficult to implement in the field (Voltage Superposition), while other methodologies present easy field application and mathematical consistency, but are considered invasive (Dominant Impedance, Capacitor Switching and Harmonic Current Injection), and can cause disturbances in the electrical grid. Seeking to combine the ideas of being a non-invasive and precise method to calculate the percentages of responsibilities, the Conservative Power Theory (CPT) proposal, applied to the sharing of responsibilities over the harmonic voltage distortions, arises. Since CPT still needs further investigation for such application, this dissertation becomes relevant. Therefore, in this work, eight distinct case studies are evaluated, using the MATLAB/Simulink software and comparing CPT with the main responsibility sharing methodologies.